Diagnosis of student understanding of content specific science areas using on-line two-tier diagnostic tests - Law, James Fisher (Curtin University, 2008)
The purpose of this research was to develop an on-line two-tier diagnostic instrument that could be used to identify alternative scientific conceptions held by students and to ascertain the conceptual level at which students are functioning. The instrument was designed to identify alternative conceptions held in relation to concepts that underpin the objectives listed in each of the four content strands of the New Zealand Science Curriculum. The stem questions of the first tier were designed around the curriculum objectives for Levels 4, 5 and 6. Distracters for the second tier were developed from alternative conceptions identified from surveys, teacher predictions and telephone interviews. A 52 item instrument was built into a Microsoft Word format with drop down menu functionality, and then transferred into an on-line format on a web site. The instrument link was sent by email to a student sample in the age range of Year 9 to 11. The student responses were analysed by answer selection and alternative conceptions were identified and classified. The instrument proved to be an economical rapid response tool for identification of student alternative conceptions to inform the design and development of student science learning programmes. The instrument and the component two-tier items have the potential to be used as part of an item bank for formative assessment tests to enhance student learning in science. The on-line functionality of the instrument has the potential to provide the 21st century learner with formative self assessment opportunities to enhance personalized self-directed learning programmes.